Correlation of the combined symptom and medication score with quality of life, symptom severity and symptom control in allergic rhinoconjunctivitis. Issue 10 (5th October 2022) - Palathumpattu, Binoy; Pieper‐Fürst, Ursula; Acikel, Cengizhan; Sahin, Hacer; Allekotte, Silke; Singh, Jaswinder; Hess, Mark; Sager, Angelika; Müller, Thomas; Mösges, Ralph
Abstract: Background: The European Academy of Allergy and Clinical Immunology recommended the Combined Symptom and Medication Score (CSMS) as primary endpoint in clinical trials on allergen‐specific immunotherapy (AIT) in allergic rhinoconjunctivitis. Here, the correlation between the CSMS and the validated standardised Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ(S)), Rhinitis Control Assessment Test (RCAT) and Visual Analogue Scale (VAS) was analysed. Methods: Two prospective, multicentre, non‐interventional studies on tree pollen, grass pollen and house dust mite allergic patients were performed. The first study comprised 167 patients receiving AIT (AIT population), and the second included 56 patients treated with symptomatic medication only (control population). For up to two seasons (pollen)/exposure periods (house dust mites), participants documented their symptoms and medication intake in a CSMS diary, including VAS. In addition, the standardised RQLQ(S) and the RCAT were completed during study visits. Results: Comparison between CSMS and RQLQ(S) revealed a positive correlation in the AIT population ( r  = 0.426) and in the control population ( r  = 0.569). For CSMS and RCAT, a negative correlation with r  = −0.409 (AIT) and r  = −0.547 (control) was shown. Positive correlation between CSMS and VAS was also demonstrated with r  = 0.585 (AIT) and r  = 0.563 (control). Conclusion: These results support the assumption that the CSMS correlates with quality of life, symptom severity and symptom control on the one hand, while the moderate strength of correlations on the other hand mirrors distinctions of the CSMS compared to the assessments used here.